2018
DOI: 10.1093/annweh/wxy081
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dermal Exposure to the Herbicide Alachlor Among Vegetable Farmers in Thailand

Abstract: Vegetable farmers applying the herbicide alachlor may be highly exposed through dermal contact when spraying. Dermal patches were attached to 10 locations on the farmers' skin when they mixed and applied alachlor in vegetable farming areas in Thailand. Measurements were made on farmers using either a backpack sprayer with a 2 stroke gasoline motor and fan or a battery operated pump. Forty-seven vegetable farmers in Bungphra subdistrict of Thailand participated in this study. Both motorized and battery pump bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…The majority of sprayers in this study were male, as has been reported in related studies of occupational paraquat exposure (Swan 1969;Howard 1982;Chester et al 1993;Lee et al 2009) mainly due to the strength needed to lift and carry the 25 liters motorized backpack for extended periods. The average sprayers in this study were middle aged, which was similar to related studies in Thailand in that young workers tend to work in the urban industrial sector, not the rural agricultural sector (Kongtip et al 2018;Mahaboonpeeti et al 2018).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The majority of sprayers in this study were male, as has been reported in related studies of occupational paraquat exposure (Swan 1969;Howard 1982;Chester et al 1993;Lee et al 2009) mainly due to the strength needed to lift and carry the 25 liters motorized backpack for extended periods. The average sprayers in this study were middle aged, which was similar to related studies in Thailand in that young workers tend to work in the urban industrial sector, not the rural agricultural sector (Kongtip et al 2018;Mahaboonpeeti et al 2018).…”
Section: Discussionsupporting
confidence: 87%
“…This could be in part because of the increased capacity (25 liters) compared with that of the battery backpack sprayers (16 to 20 liters). In addition, the motorized sprayers could produce a higher-velocity air stream with a wider range of spray droplets than battery backpack sprayers could (Mahaboonpeeti et al 2018). Additionally, a motorized sprayer may increase the fraction of respirable particles (Swan 1969).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cotton cloth (10 × 10 cm) was sewed on top of an aluminum foil pad (11 × 11 cm) at the edge. The aluminum foil pads were attached to the bare skin of sprayers with adhesive tape at 10 locations, including the forehead, upper back, right upper arm, left upper arm, right forearm, left forearm, right upper leg, left upper leg, right lower leg, and left lower leg before mixing and spraying glyphosate as shown in Figure 3 (Mahaboonpeeti et al 2018;United States Environmental Protection Agency 2009). The cotton patches were placed on the skin under the clothing farmers wore while spraying.…”
Section: Dermal Contact Samplesmentioning
confidence: 99%
“…Actual exposures derived from field-level biomonitoring studies are often far higher than what the EPA has estimated [ 56 ]. This is especially true in the case of applicators spraying pesticides with handheld and backpack sprayers [ 57 , 58 ]. A person applying one pound of pesticide active ingredient in a 6-h workday using handheld equipment will almost always experience tenfold to 100-fold higher exposure than the operator of a modern pesticide sprayer who sits in a glass-steel cab and sprays 1,000 lb of pesticide in a day [ 59 ].…”
Section: Flaws In the Science Supporting Pesticide Risk Assessment And Regulationmentioning
confidence: 99%